Features of measures to prevent fraud committed by women:: he experience of Ukraine, the European Union countries and the United States - Babanina, Viktoria; Mykytchyk, Oleksandr; Vartyletska, Inna; Bortnyk, Valentyn (DIXI, 2021)
The article analyzes approaches to the prevention of female fraud in order to identify the best ways to combat fraud committed by women. Theoretical approaches to the measures to prevent crimes committed by women, in particular, female fraud were examined. Peculiarities of the legal regulation of the prevention of female fraud in Ukraine have been studied. The conclusion was made about the insufficiency of normative acts aimed at combating female fraud in Ukraine. In addition, the investigation revealed that measures taken in Ukraine to prevent female fraud were poor and insufficient. In parallel, the experience of the EU countries and the USA in the prevention of female fraud was analyzed in the article. The programs and methods of prevention of crimes committed by women in the USA and the EU have been studied. Based on this analysis, proposals to improve approaches to the prevention of female crime, in particular, female fraud, have been developed. In particular, the conclusion was made that preventive work among the population as well as creation of special programs to work with women would be relevant.